Rebbetzin / The Rabbi’s Wife: Seen Through the Lens of Contemporary Fiction - Zucker, David J. (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2024)
Over the last five decades (the mid-1970s to the mid-2020s), a tiny number of fictional works have not only centered on the male rabbi’s spouse, but she is specifically mentioned in the title of the work. This article considers these exceptional examples: eight authors and thirteen works where the Rebbetzin or the Rabbi’s Wife is clearly featured in the title of the work.